Depression and quality of life in patients with type 2 diabetes mellitus - Mohammad Ali Bayani; Nava Shakiba; Ali Bijani; Sussan Moudi (Babol University of Medical Sciences, 2022)
Background: Depression as a frequent comorbidity in patients with diabetes requires serious attention, as failure to early detect and treat it can adversely affect the patients' complications. This study was performed to assess the prevalence of depression and quality of life in these patients. Methods: This cross-sectional study was carried-out on adult patients with type 2 diabetes mellitus referred to the endocrinology hospital clinics affiliated to Babol University of Medical Sciences, Babol, Iran, during 2018-2019. The presence and severity of depressive symptoms in patients have been assessed by Beck Depression Inventory-II; and the quality of life was measured by SF-36 questionnaire. Results: Totally, 400 patients with type 2 diabetes mellitus (300 females and 100 males) with mean age of 55.36±11.56 years were recruited. One hundred and thirty (32.5%) had depressive symptoms. Of the patients with depression, 115 (28.8%) had mild and 15 (3.8%) had moderate depression. After entering different variables in logistic regression analysis, gender (P=0.036) and ophthalmic complications (P=0.011) showed a significant association with depressive symptoms. The patients with depression had a worse quality of life compared to those who had not depressive symptoms. Quality of life score in patients with depression was significantly lower than patients without depression (p<0.0001). Conclusions: Nearly one third of the patients with type II diabetes mellitus might have depression. Diabetic patients with depression have a worse quality of life compared to those who have not depression symptoms.